MANAJEMEN PENGEMBANGAN KURIKULUM BAHASA ARAB (Studi Tentang Proses dan Mekanisme Pengembangan Kurikulum Bahasa Arab) - Moch. Yunus; Abd. Aziz (Al-Fikru : Jurnal Pendidikan Dan Sains, 2022)
When a curriculum is created and then implemented, whether the curriculum is centralized or decentralized, both have their own advantages and disadvantages. Sometimes a centralized curriculum is appropriate for a particular area, but not suitable for other regions. As in rural or remote areas, it is difficult to adjust the progress of education in urban areas.There is an opinion which says that curriculum means vehicle (currere/Latin). No matter how reliable the vehicle is made, that reliability can only be achieved if the driver is competent enough. Success, professionalism and competence are in the hands of the teacher. Because basically the curriculum was made as good as possible by the compilers.However, along with its development, the curriculum is still undergoing changes so that it is not uncommon for there to be gaps in its implementation. For this reason, with an analysis of curriculum needs, it will be known about the distance or gaps, solutions and assessment of the education curriculum in Indonesia.With the direction of writing this paper, the problems are formulated as follows: What are the stages of curriculum development?, What are the application of the principles of curriculum development? Who are the elements involved in curriculum development?Keywords: curriculum, curriculum development, Arabic Language